PENGARUH CAPITAL INTENSITY, KEPEMILIKAN MANAJERIAL, DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK - Indriyani, Iin; yusuf, Nur'aini (Jurnal Nusa Akuntansi, 2025)
This research aims to examine the effect of capital intensity, managerial ownership and company size on tax aggressiveness. In this study, tax aggressiveness is proxied using Book Tax Differences (BTD). The sample used in this study were 8 energy sector companies listed on the Indonesia Stock Exchange (IDX) for 5 years from 2019 to 2023. The research method uses a quantitative method with a purposive sampling method. The analysis technique used in this study is panel data regression analysis with a significance level of 5%. Data processing in this study used Eviews version 12 and Microsoft Excel. The best estimation model used in this study is the Fixed Effect Model (FEM). The results of this study obtained that capital intensity, managerial ownership and company size simultaneously affect tax aggressiveness. Then partially capital intensity not affects tax aggressiveness, managerial ownership does not affect tax aggressiveness, while company size affects tax aggressiveness.